Neuroprotective Roles of the Reverse Transsulfuration Pathway in Alzheimer’s Disease - Paul, Bindu Diana (Frontiers in Aging Neuroscience, 2021)
The reverse transsulfuration pathway has emerged as a central hub which integrates the metabolism of sulfur containing amino acids and redox homeostasis. Transsulfuration involves the transfer of sulfur from homocysteine to cysteine. Cysteine serves as the precursor for several sulfur-containing molecules, which play diverse roles in cellular processes. Recent evidence shows that disruption of the flux through the pathway has deleterious consequences. In this review, we will discuss the actions and regulation of the reverse transsulfuration pathway and its links to other metabolic pathways, which are disrupted in Alzheimer’s disease. The potential nodes of therapeutic intervention are also discussed, which may pave the way for development of novel treatments.